Local anaesthetic resistance in a patient with Ehlers‐Danlos syndrome undergoing caesarean section with continuous spinal anaesthesia. Issue 1 (9th June 2020) - Wloch, K.; Simpson, M.; Gowrie‐Mohan, S.
Summary: A patient with a diagnosis of Ehlers‐Danlos syndrome was scheduled to undergo elective caesarean section with a combined spinal‐epidural anaesthetic technique. The epidural attempt resulted in an inadvertent dural puncture, and we decided subsequently to place an intrathecal catheter. She required high repeated doses of hyperbaric bupivacaine (32.5 mg over 1 h) through the catheter to establish adequate sensory blockade, together with supplemental analgesic techniques. Soon after the procedure, she recovered motor function rapidly and required further supplemental analgesia. We believe this is the first report of possible local anaesthetic resistance with an intrathecal catheter anaesthetic technique for a patient with Ehlers‐Danlos syndrome. If there is resistance to the first dose of intrathecal local anaesthetic, a general anaesthetic may be the best option for such patients.